Coordination Models and Languages 15th International Conference, COORDINATION 2013, Held as Part of the 8th International Federated Conference on Distributed Computing Techniques, DisCoTec 2013, Florence, Italy, June 3-5, 2013. Proceedings - Nicola, Rocco; Julien, Christine; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 15th International Conference on Coordination Models and Languages, COORDINATION 2013, held in Firenze, Italy, in June 2013, within the 8th International Federated Conference on Distributed Computing Techniques (DisCoTec 2013). The 17 revised full papers presented were carefully reviewed and selected from 42 submissions. The papers cover a wide range of topics including coordination of social collaboration processes, coordination of mobile systems in peer-to-peer and ad-hoc networks, programming and reasoning about distributed and concurrent software, types, contracts, synchronization, coordination patterns, and families of distributed systems.
Keywords: Computer science; Computer Communication Networks; Software engineering; Operating systems (Computers).; Logic design; Computer Science; Software Engineering; Operating Systems; Computation by Abstract Devices; Logics and Meanings of Programs; Computer Communication Networks